PENGETAHUAN PARA PENIAGA KECIL TERHADAP PERMOHONAN PENSIJILAN HALAL DI NEGARA BRUNEI DARUSSALAM: SATU TINJAUAN: Small Entrepreneurs’ Knowledge of Halal Certification Applications in Brunei Darussalam: A Review - Suhaili, Suhaiella; Mohammed Fareed, Fatin Rabia'tul Adawiyah; Metusin , Norwidayawati (Jurnal Syariah, 2023)
Business conducted based on Islamic law will certainly provide many elements of benefits to fellow human beings. In order to improve the country's economy and also as a platform to develop local products, entrepreneurs are advised to generate their income through products produced to meet the needs of life. This study aims to identify the knowledge and awareness of entrepreneurs in Brunei Darussalam regarding the application of halal certificates/permits as well as the factors that cause entrepreneurs not to apply for halal certificates/permits. Quantitative methods using questionnaires are targeted at 100 small entrepreneurs engaged in online (online) and non-online (delivery) businesses. The findings of the study show that although the majority of small entrepreneurs know about the application for certificates/permits, there is also the majority of entrepreneurs who have not applied for several factors. Meanwhile, for entrepreneurs who have applied, there are several rationales that cause them to apply, which are to ensure the continuity of business and to carry out their responsibilities as Muslim entrepreneurs. This study suggests that the Bahagian Kawalan Makanan Halal (BKMH) can work with related agencies in monitoring and create a new law to enforce the Halal Certificate and Halal Label Order, to safeguard the interests of Muslim consumers.